2021
DOI: 10.1016/j.amsu.2021.102814
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features and laboratory findings first case of B. 1.617.2 (delta) variant concern (VOC) in Iraq

Abstract: Since the initial report of the severe acute respiratory syndrome (SARS CoV-2) in Wuhan, China, in 2019, the virus has constantly mutated, resulting in the appearance of novel variants. In December 2020, the B.1.617.2 (delta) variant concern (VOC) was first reported in India, and rapidly spread around the globe, is now the main brand in the United Kingdom, and it has grown dramatically. Here we present the clinical features and laboratory findings of the first case of B. 1.617.2 (delta) variant concern (VOC) i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 26 publications
2
10
0
Order By: Relevance
“…As in many other countries, the delta variant wave began to spread around to many countries [ 13 ], Libya was no exception, in late June a sharp increase in the number of positive samples was attributed to Delta, this was in agreement with our results because the frequency of Delta cases was dominant (using VIASURE SARS CoV-2Variant II assay).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…As in many other countries, the delta variant wave began to spread around to many countries [ 13 ], Libya was no exception, in late June a sharp increase in the number of positive samples was attributed to Delta, this was in agreement with our results because the frequency of Delta cases was dominant (using VIASURE SARS CoV-2Variant II assay).…”
Section: Discussionsupporting
confidence: 92%
“…B.1.617.2, termed as Delta variant by WHO, has since dominated over B.1.617.1 (Kappa variant) and other lineages[ 12 ]. The symptoms of delta infection differ from pre-existing strains, usually starting with flu-like symptoms such as sore throat, headaches, and runny nose before progressing to pneumonia [ 13 ]. Because of the higher transmissibility and mortality rate of the Delta variant, WHO alerted that this variant is rapidly becoming the main dominant strain of SARS-CoV-2 worldwide [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Wheezing and coughing were frequently noted clinical signs in infected cats, and these clinical signs tended to be more readily apparent in cats infected with the Delta variant compared to wildtype SARS-CoV-2 [26]. Clinical manifestations of experimental infection were also consistent with symptoms of upper respiratory disease observed in cats naturally infected with the Delta variant [56], and gastrointestinal signs were also observed in 3/12 cats on or after 10 dpi, reflecting similarities in clinical symptoms of humans with Delta infection [57]. While the features of diffuse alveolar damage observed on histology in all infected cats at 4 dpi is similar to our previous studies using wildtype SARS-CoV-2 [26], we also identified evidence of vasculitis and marked peri-bronchial and peri-vascular edema at 4 dpi, suggesting acute vascular injury is a prominent pathologic feature of Delta variant infection in cats as it is in humans.…”
Section: Discussionsupporting
confidence: 53%
“…Another study reported the first case of delta variant B.1.617.2 in Iraq which was detected in a 6 years old female who presented at the hospital with fever, headache, severe abdominal pain, vomiting, and diarrhea. She was successfully treated and was discharged from the hospital in good condition ( Essa et al, 2021 ). In Bahrain, AlGhoozi et al reported a case where SARS-CoV-2 infection was possibly the trigger of Henoch-Schonlein purpura in a 4 years old boy ( AlGhoozi and AlKhayyat, 2021 ).…”
Section: Childrenmentioning
confidence: 99%